2005
DOI: 10.1007/s00439-005-1300-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: correlation between structural changes in α-galactosidase, and clinical and biochemical phenotypes

Abstract: Fabry disease comprises classic and variant phenotypes. The former needs early enzyme replacement therapy, and galactose infusion is effective for some variant cases. Attempts of early diagnosis before manifestations appear will begin in the near future. However, it is difficult to predict the phenotype, to determine the therapeutic approach, only from genetic information. Thus we attempted structural analysis from a novel viewpoint. We built structural models of mutant alpha-galactosidases resulting from 161 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…[18][19][20][21][22] We defined that the structure was influenced by an amino acid substitution when the position of an atom in a mutant differed from that in the wild-type structure by more than the cut-off distance (0.15 Å ) on the basis of the total root-mean-square distance (RMSD), as described earlier. [18][19][20][21][22] The numbers of influenced atoms in the main chain and the side chain were calculated. Abbreviations: ASA, solvent-accessible surface area; RMSD, root-mean-square distance; À, no protein; ¼, normal amount; m, more than normal; k, less than normal.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21][22] We defined that the structure was influenced by an amino acid substitution when the position of an atom in a mutant differed from that in the wild-type structure by more than the cut-off distance (0.15 Å ) on the basis of the total root-mean-square distance (RMSD), as described earlier. [18][19][20][21][22] The numbers of influenced atoms in the main chain and the side chain were calculated. Abbreviations: ASA, solvent-accessible surface area; RMSD, root-mean-square distance; À, no protein; ¼, normal amount; m, more than normal; k, less than normal.…”
Section: Methodsmentioning
confidence: 99%
“…Each mutant model was then superimposed on the wild-type structure based on the Ca atoms using the least-square-mean fitting method. 31,32 We reported that the structure was influenced by an amino-acid substitution when the position of an atom in a mutant differed from that in the wild type by more than the cutoff distance (0.15 Å ) on the basis of the total RMSD, as described previously. 32 We calculated the numbers of influenced atoms in both the main chain and the side chain.…”
Section: Structural Modeling Of the Human B-gal Proteinmentioning
confidence: 75%
“…The analysis was based on the differences between the wild types and mutants to determine the influence of the amino-acid substitutions geographically and semi-quantitatively according to the method described previously. 32 …”
Section: Color Imaging Of the Atoms Influenced By The Amino-acid Subsmentioning
confidence: 99%
“…Por exemplo, diferentes mutações estão associadas a fenó-tipos similares, enquanto membros de uma família que compartilha a mesma mutação apresentam diferentes fenótipos. 7,13 Quando se suspeita do diagnóstico de DF, a pesquisa da história familiar é muito importante, já que a maioria dos casos ocorre de forma hereditária. Porém a ausência de dados familiares positivos não invalidam o diagnóstico, uma vez que mutaçoes têm sido documentadas.…”
Section: Genéticaunclassified